Factors contributing to accident among local and foreign workers in manufacturing industry Pekan Nanas - Loo, M. K. (2014)
This research aims to determine the factors contributing to accident among local and foreign workers in manufacturing industry and identify the mean difference of gender between the groups and within the groups of local and foreign worker. This research was through questionnaire to analyzed using Package for Social Science (SPSS) software. 285 respondents answered questionnaire. The result of this study indicates that job-related accident is the main factor contributing to accident in manufacturing industry. It was followed by individual-related accident, organization-related accident and environment-related accident. Moreover, means difference of gender between the groups and within the groups of local and foreign worker shown that female worker contributing to accident in manufacturing industry is higher than male worker.